Factors Influencing Customer Satisfaction: A Case Study of Perodua - Kuek, Thiam Yong; Teoh, Kok Ban; Tnay, Alicia Ai Xian; Ti, A Yee A/P A; Peedikayil, Adeeb Valliyapurayil; Mohamad Zaki, Aiman Hakim Bin; Azizul Jasri, Akhtar Izzeti Binti; Ali, Anees Jane; Mui Hung Kee, Daisy (Advances in Global Economics and Business Journal, 2025)
Perusahaan Otomobil Kedua Sdn Bhd or Perodua was founded in 1993. It is Malaysia's largest and first Energy-Efficient Vehicle (EEV) manufacturer. The company aims to provide Malaysians with full mobility through high-quality, useful products and services. The recent Daihatsu testing scandal raised concerns among Perodua customers, as it seemed to implicate Perodua vehicles. Although Malaysia’s Road Transport Department has cleared Perodua of any involvement in the scandal it remains essential to assess customer satisfaction with Perodua vehicles in light of this incident or other similar incidents in the future. Thus, this study attempts to explore the factors that affect customer satisfaction with emphasis on trust, brand image, perceived price fairness, and customer service as the factors. 150 Perodua customers participated, completing the quantitative research through a self-administered questionnaire. The collected data was analysed using SPSS software based on multiple regression analysis. The results showed that trust, brand image, and perceived price fairness greatly influence Perodua's customer satisfaction. With the ultimate goal of increasing customer satisfaction and competitive advantage in the automotive industry